Brief Maternal Separation Inoculates Against the Effects of Social Stress on Depression-Like Behavior and Cocaine Reward in Mice - Calpe-López, C.; Martínez-Caballero, M. A.; García-Pardo, M. P.; Aguilar, M. A. (Frontiers in Pharmacology, 2022)
Exposure to intermittent repeated social defeat (IRSD) increases the vulnerability of mice to the rewarding effects of cocaine in the conditioned place preference (CPP) paradigm. According to the “inoculation of stress” hypothesis, a brief period of maternal separation (MS) can provide protection against the negative effects of IRSD. The aim of the present study was to assess whether exposure to a brief episode of MS prevents the subsequent short-term effects of IRSD on depression- and anxiety-like behaviors and to explore its long-term effects on cocaine CPP in mice. Four groups of male C57BL/6 mice were employed; two groups were separated from their mother (6 hours on postnatal day (PND) 9), while the other two groups were not (controls). On PND 47, 50, 53 and 56, mice that had experienced MS were exposed to social defeat in the cage of an aggressive resident mouse (MS+IRSD group) or were allowed to explore an empty cage (MS+EXPL group). The same procedure was performed with control mice that had not experienced MS (CONTROL+IRSD and CONTROL+EXPL groups). On PND57-58, all the mice performed the elevated plus maze and the hole-board, social interaction and splash tests. Three weeks after the last episode of defeat, all the mice underwent the CPP procedure with cocaine (1 mg/kg). Irrespective of whether or not MS had taken place, a reduction in open arms measures, dips, and social interaction was observed in mice that experienced IRSD. A lower frequency of grooming and acquisition of cocaine-induced CPP was observed only in mice exposed to IRSD alone (CONTROL+IRSD). These results suggest that exposure to a brief episode of stress early in life increases the subsequent resilience of animals to the effects of social stress on depression-like behavior and vulnerability to cocaine.